The Implementation of a Management Information System Based on Digital Madrasah Report Cards at MTS Muhammadiyah Malino - Ahmad Fauzi Yusri (Eduvest - Journal of Universal Studies, 2025)
This research examined the implementation of a management information system using digital madrasah report cards at MTs Muhammadiyah Malino, focusing on three main aspects: how the system was implemented, the supporting and hindering factors, and its impact. This qualitative study employed observation, documentation, and interviews with the head of the madrasah, the vice principal for curriculum, the operator, class advisers, and educators. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The findings indicated that the implementation of this system was relatively successful in both planning and execution. The head of the madrasah conducted socialization sessions, and the operator received district- and provincial-level training before implementation. During execution, administrative staff assisted teachers in overcoming difficulties, and system usage was scheduled in turns to minimize server issues. Key supporting factors included the availability of computers that met the system’s requirements and a stable internet connection. This study recommends that the Ministry of Religious Affairs improve the digital madrasah report card application to facilitate student and parent access. The madrasah head and operator should ensure adequate training for teachers in managing educational digitalization. Additionally, infrastructure support and human resource readiness must be strengthened to optimize the system’s implementation.